An analysis of cooperative R&D in the United States - Miyata, Yukio (Technovation)
This paper investigates the willingness of US firms to participate in cooperative R&D by cross-industry data and a case study of SEMATECH. The cross-industry analysis results indicate that there is no strong relationship between cooperative R&D and R&D diversification; however, there are strong positive relationships between cooperative R&D and industry's R&D resource costs, the necessity of basic research and standardization, both of which have a spillover problem, and the existence of foreign competitors. SEMATECH, which was organized by major US semiconductor manufacturers, was the first federally subsidized cooperative R&D project. Sharing R&D costs, competing with Japanese firms, and mitigation of spillover problems are important reasons for firms to participate in SEMATECH, agreeing with the finding from the cross-industry study. SEMATECH helped the United States to develop semiconductor processing technology in parity with the Japanese. However, as the threat of Japanese competitors declined, US firms decided to scale down SEMATECH rather than leapfrog the Japanese technology.